Penerapan Metode Talaqqi dalam Meningkatkan Kemampuan Menghafal Al-Qur’an Juz 30 di TPQ Nurul Hikmah Sampang Sempor Kebumen - Fahmi, Zainul; Mahfudz, Ali (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
This research is a Classroom Action Research (CAR). The background of this research is based on observations carried out at TPQ Nurul Hikmah Sampang that the interest in memorizing students is still lacking, students reason that they cannot read their letters, students think that memorizing is difficult, and low learning outcomes. In the process of memorizing lessons the teacher directly invites students to memorize together. Therefore, an appropriate teaching method is needed. This Classroom Action Research (CAR) uses the talaqqi method. The research was conducted in 2 cycles. Each cycle consists of planning, implementing actions, observing, and reflecting. The research subjects were students of level II and III at TPQ Nurul Hikmah Sampang, totaling 22 students. Sources of data come from students, teachers, and observers. Data collection techniques with observation, interviews, tests, and documentation. Data analysis techniques namely data reduction, data presentation, and verification. The results showed that the application of the talaqqi method could improve the memorization ability of level II and III students at TPQ Nurul Hikmah Sampang. Based on the research, information can be obtained that there was an increase in the results of the oral test in cycle I indicating that there were 14 students who passed or 63.64% with an average score of 75.82. Then in cycle II it showed that 19 students or 86.36% of students passed with an average value of 86.64.